2017
DOI: 10.1097/md.0000000000008905
|View full text |Cite
|
Sign up to set email alerts
|

Fimasartan-induced liver injury in a patient with no adverse reactions on other types of angiotensin II receptor blockers

Abstract: Rationale:Angiotensin II receptor blockers (ARBs) are widely used for patients with hypertension, and fimasartan is a recently approved ARBs. Fimasartan can cause headache, dizziness, itching, and coughing. There have been several reports of hepatotoxicity in ARBs. However, there have not yet been published reports of the hepatotoxicity of fimasartan.Patient concerns:A 73-year-old man with hypertension experienced liver injury after fimasartan administration. He had a previous history of taking 3 types of ARBs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…Furthermore, there have been concerns that fimasartan might be related to liver toxicity due to its predominant hepatobiliary excretion. 13,20,21 The results of this prospective study provide reliable evidence that fimasartan could be a safe choice for long-term treatment of HTN, regardless of underlying liver disease.…”
Section: Discussionmentioning
confidence: 64%
See 3 more Smart Citations
“…Furthermore, there have been concerns that fimasartan might be related to liver toxicity due to its predominant hepatobiliary excretion. 13,20,21 The results of this prospective study provide reliable evidence that fimasartan could be a safe choice for long-term treatment of HTN, regardless of underlying liver disease.…”
Section: Discussionmentioning
confidence: 64%
“…32 Fimasartan has also been reported to have caused liver damage in a patient who had tolerated previous ARB use. 13 According to previous Figure 2 The risk of adverse events according to chronic liver disease is not significantly different between exploratory subgroups. Abbreviations: OR, odds ratio; CI, confidence interval.…”
Section: Discussionmentioning
confidence: 66%
See 2 more Smart Citations
“…To date, few case reports have described ARB-induced liver injury. 9 10 11 12 Most cohort studies have not reported detailed liver injury incidence and outcomes related to ARB-related DILI, instead only the overall, severe adverse drug-related reaction rates have been reported. 8 …”
Section: Introductionmentioning
confidence: 99%